Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1097/00004836-199610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Antimitochondrial Antibody—Negative Chronic Nonsuppurative Destructive Cholangitis

Abstract: We investigated whether autoimmune cholangitis (AC) has specific features that constitute an entity other than primary biliary cirrhosis (PBC). We compared clinical, laboratory, and liver biopsy features; response to treatment; and the follow-up of two groups of patients. The first group comprised seven patients with AC criteria-PBC with negative antimitochondrial antibodies (AMAs) and positive antinuclear antibodies (ANAs)-termed the PBC AMA-negative group; the second was made up of another seven PBC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Viral infectious in animals have provided suitable infectious disease models for the induction of autoimmune destruction of ␤ islet cell, and infections with enteroviruses, such as echovirus 9 and Coxsackie B3 and B4 virus, have been linked with type I diabetes in children and young adolescents (3)(4)(5)(6). Genome scanning studies have shown that the human leukocyte antigens (HLA) genes within the major histocompatibility complex provide the most prominent linkage associated with type I diabetes; the extended haplotype DR4, DQA3, DQB3/2 reportedly provides a 5-to 35-fold increased relative risk for disease (7). In addition, polymorphisms in the promoter region of the insulin gene are associated with the development of type I diabetes (8).…”
Section: Positive Markers In Ama-negative Pbcmentioning
confidence: 99%
“…Viral infectious in animals have provided suitable infectious disease models for the induction of autoimmune destruction of ␤ islet cell, and infections with enteroviruses, such as echovirus 9 and Coxsackie B3 and B4 virus, have been linked with type I diabetes in children and young adolescents (3)(4)(5)(6). Genome scanning studies have shown that the human leukocyte antigens (HLA) genes within the major histocompatibility complex provide the most prominent linkage associated with type I diabetes; the extended haplotype DR4, DQA3, DQB3/2 reportedly provides a 5-to 35-fold increased relative risk for disease (7). In addition, polymorphisms in the promoter region of the insulin gene are associated with the development of type I diabetes (8).…”
Section: Positive Markers In Ama-negative Pbcmentioning
confidence: 99%
“…40 Over subsequent years, increasing numbers of patients with similar presentations have been described as "primary autoimmune cholangitis," 13,41,42 "autoimmune cholangiopathy," 43 or AMA-negative PBC. 14,44,45 The principal discriminant from classical PBC in all of these studies is the lack of AMA. In one study 32% of patients with PBC were found to be AMA negative 13 ; however, this is probably skewed by the specialist referral practice of the Ishak.…”
Section: Autoimmune Cholangitis: a Crossover Between Pbc And Aih Or Amentioning
confidence: 99%
“…13,14,41,44 A total of 13 patients with AMA-negative PBC or "autoimmune cholangitis" 14,110,111 were treated with UDCA, and showed biochemical improvements indistinguishable from those of similarly treated AMA-positive PBC patients. However, in other reported series, immunosuppression has been given in view of the high ANA titers with improved clinical and biochemical markers in 2 studies 43,44 that included 7 patients in total, but with only transient biochemical improvement in 1 of 13 patients combined from 2 other series. 39,41 In only 4 patients were follow-up biopsies available after immunosuppressive treatment, and showed diminished hepatitic features but no improvement of bile duct damage.…”
Section: Treatment Of Overlap Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Indeed, autoimmune cholangitis has been variously categorized as a variant of primary biliary cirrhosis (PBC) 4,[6][7][8] or autoimmune hepatitis (AIH), 5,9 a hybrid of both, 10 and a separate disease entity. 2,3,11 Patients with autoimmune cholangitis have been distinguished from patients with PBC by having higher serum levels of aspartate transaminase (AST) and lower serum concentrations of immunoglobulin M. 2 They also have been characterized by the presence of antibodies to carbonic anhydrase in serum, 12 HLA risk factors that are different from PBC, 13 and clonal expansion of liver-infiltrating lymphocytes that express V␤5.1 T-cell receptors. 14 These findings have suggested that autoimmune cholangitis is an entity distinct from PBC and not an ''AMA-negative'' variant.…”
mentioning
confidence: 99%